Microbiota transfer early after birth modulates genetic susceptibility to chronic arthritis in mice - Borrego, Andrea; Koury Cabrera, Wafa Hanna; Souza, Alanis Tiozzo; Eto, Silas Fernandes; de Oliveira, Silvio Luis [UNESP]; Rodrigues, Josias [UNESP]; Jensen, José Ricardo (Elsevier, 2025)
Genetics is central to the susceptibility or resistance to autoimmunity, and mounting evidence indicates that the intestinal microbiota also plays an essential role. In murine arthritis models, short-chain fat acid supplementation reduces disease severity by modulating tryptophan-metabolizing bacteria. Common microbiota transfer methods modulate arthritis severity, however, they are not practical for chronic models such as pristane-induced arthritis (PIA). PIA-resistant (HIII) and PIA-susceptible (LIII) mice harbor diverse intestinal microbiomes, which might be implicated in their divergent susceptibility. To investigate this hypothesis, we used cross-fostering to stably transfer the microbiota. In this study, we show that extreme susceptibility to arthritis can be modulated by early microbiota transfer, with long-lasting effects. HIII and LIII pups were cross-fostered and injected with pristane after weaning. PIA severity in cross-fostered LIII mice was significantly reduced in the chronic phase. Metagenomic analyses showed that HIII and LIII microbiomes were partly shifted by cross-fostering. Microbial groups whose abundance was associated with either HIII or LIII mice presented similar composition in cross-fostered mice of the opposite strains, suggesting a role in PIA susceptibility. Identification of bacterial groups that modulate chronic arthritis will contribute novel insights on the pathogenesis of human rheumatoid arthritis and targets for replication and functional studies.
Keywords: Arthritis; Experimental; Gut microbiota; Mouse; Pristane